Cutaneous metastases with different clinical presentations: case series and review of the literature - Icim Komurcugil; Zulkuf Arslan; Zulal Inci Bal; Mert Aydogan; Yagmur Ciman (PAGEPress Publications, 2022)
Cutaneous metastasis (CM) is a rare clinical entity with an incidence of less than 10% among oncology patients. Dissemination to the skin can be via bloodstream, lymphatics, direct expansion or by seeding after surgical procedures. Skin metastases usually develop months to years after the diagnosis of the primary tumour while it may be the opposite in some rare cases. CM has various clinical presentations; diagnoses can be easily overseen as CM can mimic other dermatologic diseases. Herein, we present five different cutaneous metastasis cases, each with distinct dermatological presentation. Our main aim here is to allow dermatologists consider skin metastases in the differential diagnoses of dermatological diseases, in their clinical practice.